Hydrological Processes Simulation at Plot Scale Using The Smap Model In The Semiarid | Simulação de processos hidrológicos na escala de lotes usando o modelo Smap em semi-árido - Lopes, Iug; Montenegro, Abelardo A.A. (Revista Geama, 2017)
Vegetation cover plays an important role on overland flow generation and erosion, directly impacting infiltration and soil water storage. The objective of this study was to investigate hydrological processes and soil moisture dynamics through conceptual modelling in intensively monitored experimental plots under natural rainfall with different soil cover conditions, in the Brazilian semiarid. Soil moisture was monthly monitored using a CPN 503 DR Neutron Probe device. Calibration curves previously defined were adopted for moisture assessment. Four experimental soil cover treatment were established: Cactus “Palma” barriers (PB); mulching (MC); Bare soil (BS) and natural vegetation cover (NC). Nash-Sutcliffe (ENS) coefficient and PBIAS index were adopted to assess hydrological processes analysis. The SMAP model successfully predicted the flow and humidity of the experimental plots for the natural cover and Mulching coverage, with a global ENS index of over 0.877. Scenarios of changes in soil cover have dramatically affected the modeling of water resources in the plots. The present study was important to improve the understanding and distinct hydrological processes relevance under different cover conditions in experimental plots in the semiarid.